A percepção da administração do Serviço Social Autônomo sobre a gestão de riscos como um instrumento para a tomada de decisão - Oliveira, Luciane Dutra (Universidade do Vale do Rio dos Sinos, 2020)
This research analyzes the impact of the implementation of the risk management process on the perception of managers and employees involved in the strategic formulation of an Autonomous Social Service (SSA) company. A sample of 86 administrators and employees answered a survey in two phases of data collection, Phase I during the implementation of the process and Phase II after the implementation of the process was completed. The results show that managers and employees perceive the importance of risk management permeating the company's activities and that it adds value in strategic decision-making. However, there was no change in the respondents' perception of risk management after the implementation of the process in the company.
Keywords: Gestão de riscos; Estratégia; Percepção; Tomada de decisão; Serviço Social Autônomo; Risk management; Strategy; Perception; Decision making; Autonomous Social Service; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis